Changing Continentality in Europe between 1938-2018 - Vajs, Tanja (Journal for Geography, 2019)
The article analyzes continentality changes in Europe in the period between 1938 and 2018. We use the raw data of monthly air temperature averages, obtained from the website: European Climate Assessment & Dataset, collected by 443 climate stations. The data is processed with the program MATLAB and the results are plotted with Excel and ArcGIS. The results show that there are differences between the Supan, Gorczynski and Conrad Continentality Indices. We also found that in the period from 1938 to 2018, the trends of continentality indices have changed. Our results have shown that the climate in some parts of Europe is becoming more maritime, especially in the Northern and Eastern regions, while in other territories it is becoming more continental, especially in the Mediterranean coastal regions.